2022
DOI: 10.1515/applirev-2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

The mundanity of translanguaging and Aboriginal identity in Australia

Abstract: Drawing on ethnographic interview analysis of Aboriginal participants in Australia, this study seeks to expand the critical discussions in Applied Linguistics by understanding the concept of translanguaging in relation to its “mundanity” (or ordinariness). Our data shows that rather than perceiving translanguaging as extraordinary, for Aboriginal speakers it is more likely to be considered normal, unremarkable, mundane, and as a long-existing phenomenon. The concept of the mundanity of translanguaging is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…More theoretical work is needed to elevate translanguaging and decolonisation from subaltern theories to mainstream theories, and to apply them in a national project that affects and involves people from all backgrounds. It is also important to remember that although translanguaging practices containing the Indigenous language have become an ordinary practice for Indigenous peoples in settler countries (Seals & Olsen-Reeder, 2020;Tankosić et al, 2022;Wigglesworth et al, 2011), it may not be common among other ethnic communities. It cannot be taken for granted that every teacher and student is capable of translanguaging between Māori and English or is well-versed in Indigenous languages when no formal or mandatory training is provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More theoretical work is needed to elevate translanguaging and decolonisation from subaltern theories to mainstream theories, and to apply them in a national project that affects and involves people from all backgrounds. It is also important to remember that although translanguaging practices containing the Indigenous language have become an ordinary practice for Indigenous peoples in settler countries (Seals & Olsen-Reeder, 2020;Tankosić et al, 2022;Wigglesworth et al, 2011), it may not be common among other ethnic communities. It cannot be taken for granted that every teacher and student is capable of translanguaging between Māori and English or is well-versed in Indigenous languages when no formal or mandatory training is provided.…”
Section: Discussionmentioning
confidence: 99%
“…In teaching, teachers supported embedding cultures and worldviews Indigenous to New Zealand to genuinely engage Māori students in their classes. In particular, the two teachers in low-decile schools with more Indigenous students from low socioeconomic families found that this new policy was already reflected in the mundanity of their everyday teaching practices (Tankosić et al, 2022). They shared examples of how they enacted translanguaging involving Chinese, English, and te reo Māori to give instruction in class and engage students in learning activities.…”
Section: Teachers' General Attitudes Towards Integrating Mātauranga M...mentioning
confidence: 99%
“…This perspective also suggests an awareness of the power that language has in defining cultural and personal identity. Recognizing the potential for language to empower or marginalize CSL writers is important in developing a translingual identity (Tankosić, 2022;Tankosić et al, 2022;Zheng, 2017) to appreciate the fluidity and synergy of language resources in producing unique and creative ideas.…”
Section: Identity Formationmentioning
confidence: 99%
“…With her co-author Gelderen, they describe how this resource can be used for a 'Lonydju'yirri (side-by-side) multi-literacy and transcultural approach. A small number of other studies have explored the impact of traditional language use and AAE on developing positive self-identity (e.g., Oliver & Exell, 2019Tankosić et al, 2022). It also should be noted that because of the burgeoning interest of applied linguists concerning unique contexts, as with the other themes described in this review, several Australian researchers working with Aboriginal and Torres Strait Islander participants have published their work internationally, rather than in national journals (e.g., Disbray & Martin, 2018;Macqueen et al, 2019;Oliver et al, 2021;Simpson & Wigglesworth, 2018;Steele et al, 2022).…”
Section: Teaching and Learning Traditional Languagesmentioning
confidence: 99%
“…Understanding international students' experience in Australia through their translingual practices and processes is critical for classroom practices and activities. The significance of these studies lies in the normalisation of translanguaging by people from different backgrounds as a way for them to maintain their cultural and linguistic diversity (Tankosić et al, 2022).…”
Section: Translanguagingmentioning
confidence: 99%